Dynamic Analysis of the Rental Prices of Long-Rental Apartments and Ordinary Rental Housing Based on the Impact of Long-Rental Apartment Enterprises’ Competitive Behaviors - Lingling Mu; Xiangyu Qin; Yaoyao Wang (Discrete Dynamics in Nature and Society)
This paper addresses the issue of the impact of the competitive behaviors of long-rental apartment firms on the rents of long-rental apartments and ordinary rental housing and introduces a dynamic gaming approach to the housing rental market domain to reveal changes in the long-term complexity of rents of long-rental apartments and ordinary rental housing caused by the competitive behavior of long-rental apartment firms. Through numerical simulation, it is found that the adoption of smaller rent adjustment strategies by firms is important for maintaining system stability, while the changes in reference effect behavior of landlords and service quality and differences in demand share have moderating effects on system stability. The enhanced reference effect of landlords, the improvement of service quality, and the increase of the difference in demand share between the two long-rental apartments help to mitigate the disruption of system stability by the increase of the adjustment factor of the firms. The decentralized long-lease apartment firms, which occupy a higher proportion of the market, are able to exert a major impact on the rent of general rental housing by taking advantage of the market, while the difference in the demand share between the two firms is the main reason for the change in the rent of long-rental apartments.